MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN VIDEO UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI SISTEM PERNAPASAN - Siti Alhusna Nurul Agustin; Kurnia Ningsih; Eko Sri Wahyuni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
Abstract This study was aimed to determine the process of implementation of learning and improvement of students’ learning outcomes with guided inquiry learning model assisted video on the material of the Respiratory System at class VIII B of SMP Negeri 10 Pontianak. The method was the class action research, while subject of this research was all of students of class VIII B SMP Negeri 10 Pontianak academic year 2016/2017 which consists of 38 students. This study was conducted in two cycles which each cycle consists of four stages namely planning, acting, observing and reflecting. Data collection techniques were the measurement, observation, interview, documentation, with the instrument of written test of multiple choices that consists of 20 questions and observation sheet of learning process. The results of data analysis showed that the implementation of guided inquiry learning model can improve students’ learning outcomes, the students’ improvement is 71.05% in the first cycle and 89.47% in the second cycle. The implementation of learning process in the first cycle was 95% and the second cycle was 100%. Thus it can be said that the students’ learning outcomes and learning implementation process had achieved the expected performance indicators.Keywords: Guided inquiry learning, learning outcomes, respiratory system